A gendered ecosystem services approach to identify novel and locally-relevant strategies for jointly improving food security, nutrition, and conservation in the Barotse Floodplain - Estrada-Carmona, Natalia; Attwood, Simon; Cole, Steven M.; Remans, Roseline; DeClerck, Fabrice A.J. (Informa UK Limited, 2020)
Multiple lines of evidence call for the use of locally-relevant strategies to guide and support sustainable agricultural intensification while improving development and conservation outcomes. The goal of this study was to identify the ecosystem services from natural and agricultural systems to achieve this aim in the Barotse Floodplain of Zambia. Our methodology utilized a gender-sensitive ecosystem services approach, whereby local knowledge from women and men was harnessed to understand which services and their sources are important. In addition, we identified the various constraints and options people encounter for developing sustainable and nutritious agriculture while achieving conservation outcomes. The results of our study indicate that the floodplain provides a broad range of ecosystem services, which are important for securing local livelihoods and wellbeing. The forests in the uplands and the grasslands in the plains are the primary sources of the 17 provisioning and regulating ecosystem services assessed. Nonetheless, both are often converted to agriculture due to their high soil fertility. We identified opportunities and challenges for sustainable agricultural intensification and development in areas with lower conservation concerns. We discussed the constraints and limitations for promoting sustainable and inclusive agriculture in those areas.